A Case Study Analysis of Separation Anxiety in the Effect of the Maternal and Paternal Role on Separation Anxiety in Early Childhood - Elena Drazheva (The Global Psychotherapist, 2025)
This article looks at how young children experience separation anxiety by comparing two real-life cases: one of a child with a strong emotional connection to the mother, and another whose father plays an active role in caregiving. The aim is to understand how different patterns of attachment and family dynamics influence the intensity of anxiety reactions. Observations were gathered through everyday behaviour monitoring, conversations with parents, and expressive techniques such as adapted emotion-rating scales and family drawing activities. The therapeutic process was based on Positive Psychotherapy, with a focus on helping the children become more aware of their emotions, build inner coping skills, and see their anxiety in a new, more manageable light. The comparison shows how varied parenting involvement can shape children's ability to regulate emotions and build resilience when faced with separation.